Budownictwo zrównoważone w mieście – oszczędność i racjonalizacja - Tokarski, Daniel (Public participation in urban climate policy making: The example of Lodz, 2024)
The aim of the study is to systematize knowledge about the rationalization of construction in Poland. Based on the literature review, the author identifies guidelines and indicates all regulations regarding the design of energy-efficient buildings, with particular emphasis on the legal conditions for energy performance, thermal modernization and energy audits of buildings. The text introduces the theories of low-energy, sustainable and ecological construction and shows that properly planned and implemented investments can meet legal requirements and reduce operating costs, without sacrificing comfort of use. The publication combines an interdisciplinary approach from the areas of engineering and technical sciences and social sciences.